A 6.89-MHz 143-nW MEMS Oscillator Based on a 118-dBΩ Tunable Gain and Duty-Cycle CMOS TIA - Ahmed Kira (MDPI AG, 2021)
This article presents a 6.89 MHz MEMS oscillator based on an ultra-low-power, low-noise, tunable gain/duty-cycle transimpedance amplifier (TIA) and a bulk Lamé-mode MEMS resonator that has a quality factor (Q) of 3.24 × 106. Self-cascoding and current-starving techniques are used in the TIA design to minimize the power consumption and tune the duty-cycle of the output signal. The TIA was designed and fabricated in TSMC 65 nm CMOS process technology. Its open-loop performance has been measured separately. It achieves a tunable gain between 107.9 dBΩ and 118.1 dBΩ while dissipating only 143 nW from a 1 V supply. The duty-cycle of the output waveform can be tuned from 23.25% to 79.03%. The TIA has been interfaced and wire bonded in a series-resonant oscillator configuration with the MEMS resonator and mounted in a small cavity standard package. The closed-loop performance of the whole oscillator has been experimentally measured. It exhibits a phase noise of −128.1 dBc/Hz and −133.7 dBc/Hz at 1 kHz and 1 MHz offsets, respectively.